PEMANFAATAN BUAH PEDADA (Sonneratia caseolaris) DAN BUAH NAGA MERAH (Hylocereus polyrhizus) DALAM PEMBUATAN FRUIT LEATHER - Roby ' Rahman; Usman ' Pato; Noviar ' Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to get the best combination of crabapple mangrove (Sonneratia caseolaris) and red dragon fruit (Hylocereus polyrhizus).  The research used a Completely Randomized Design (CRD) with four treatments and four replications. The treatments were PNm1 (ratio numbers crabapple mangrove and red dragon fruit tingles 100 : 0), PNm2 (ratio numbers crabapple mangrove and red dragon fruit tingles 75 : 25), PNm3 (ratio numbers crabapple mangrove and red dragon fruit tingles 50 : 50) dan PNm4 ratio numbers crabapple mangrove and red dragon fruit tingles 25 : 75). The data obtained were analyzed statistically using Anova and DNMRT at 5% level.  The results show that use of crabapple mangrove and red dragon fruit significantly affected on moisture, ash contents, acidity (pH), sucrose contents crude fiber contents and organoleptic test. The best treatment of fruit leather from this research was PNm2 which had moisture 17,89%, ash contents 0,92%, acidity (pH) 3,53, sucrose contents 57,31%, crude fiber contents 6,95%, red color, a little bit crabapple mangrove flavour, acidity sweetness taste, the texture was a little bit springy and assessment of color, flavor, taste and texture of fruit leather was preferred by the panelist’s.   Keyword: fruit leather, crabapple mangrove, red dragon fruit